Frontline mobilisation as border thinking: redefining just transitions through decolonial praxis and community organising - Cleovi C. Mosuela (Global Social Challenges Journal)
I analyse the coming together of frontline actors, particularly people of colour in the US, building on the concept of ‘just transitions’ to help solve the climate crisis as ‘border thinking or border epistemology’ within decolonial thought. Frontline communities are characterised by high exposure to climate and environmental risks; fewer safety nets because of their immigration status and insecure jobs; and less political power to respond to risks. My contribution is twofold: first, to allow reflexivity and to acknowledge that I share some sense of the lived experiences with the people I speak with in my research, I have approached our encounter through pakikipagkapwa, a Filipino indigenous concept that evokes concepts of communal support, solidarity and equality. Second, I argue that conceptualising frontline mobilisation as border thinking repositions frontline actors as creators, thinkers and knowers who harness their collective power to shift from an extractive economy, which is profiting off labour and natural resources with centralisation of profits, to a regenerative one that is ecologically and equitably sustainable. Through praxis and community organising, frontline communities reclaim their agency, challenge dominant neoliberal capitalistic relations and redefine just transitions that reflect their practices and vision of the world.